The Principal's Leadership Style on the Quality of Educational Administration Services in Muslim Schools - Yenni, Yenni; Irma Suryani Siregar; M. Yem Mardhatillah (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2025)
This article aims to find out how and to what extent the school leadership style abilitiesinfluence the quality of educational administration services. This type of research is quantitative, research data is collected using a Likert scale model instrument which has been tested for validity and reliability, research data is analyzed statistically using simple linear regression analysis techniques assisted by SPSS 16, the samples for this research are all administrative staff at muslim school, teachers, students and parents/guardians of 36 students. The results of the research prove that the influence of the leadership style ability on the quality of educational administration services is 15.1%, so it is included in the very low but influential category. This means that there is a significant relationship between variables X and Y. Research findings illustrate that the leadership style of educational institution leaders influence the quality of service provided by educational institutions to their customers. These findings also occur in government institutions that provide services to the public. Several previous research findings convey the same thing. This is also proven in the findings of this research. The conclusion of this article is that the leadership style of school principals influence the quality of educational administration services at the institution concerned.